Role of mutant p53 and autophagy on precancerous lesions of gastric cancer progression - Qiuyue Wang; Yutao Wu; Wenrong Wang (Medicine, 2026)
Precancerous lesions of gastric cancer (PLGC) represent a critical stage in the development of gastric cancer. Multiple complex factors working together can increase the risk of cancer progression. Relevant published papers were collected through a search of the PubMed, Google Scholar, and Web of Science databases. Recent studies have shown that mutant p53 can impede processes like cell cycle arrest, cell apoptosis, and DNA damage repair, which promotes the proliferation of cancer cells and influences the transition from PLGC to gastric cancer. Autophagy, a process of lysosomal degradation for abnormal proteins or damaged organelles, exhibits dual roles in the process of carcinogenesis (either promoting cell death or facilitating survival). Based on recent research findings, this article systematically discusses the critical roles of mutant p53 and autophagy in the development of PLGC. It also addresses the cross-regulatory relationship between mutant p53 and autophagy, wherein mutant p53 inhibits autophagy, and the regulation of autophagy, in turn, affects the stability of mutant p53. These insights may provide new theoretical support and potential therapeutic strategies for the early prevention and treatment of gastric cancer.